AN ANALYSIS OF TRAFFIC ACCIDENT RATES IN DUMAI, RIAU PROVINCE - Zaini, Abdul Kudus; Faza, Sri Uswatun Hasanah (PT. Jurnal Center Indonesia Publisher, 2025)
Roads, including land, sea, and air transport, are vital in the overall transportation system. However, a lack of focus on safety can lead to increased traffic accidents. This study analyzes accident data from five Dumai (Riau Province) roads with the highest accident rates. The analysis used secondary data, including traffic accident records and average daily traffic (ADT) from 2019 to 2023. The study followed a descriptive method with data collection through observation and documentation. The findings show that Soekarno Hatta Street experienced the highest number of accidents, totaling 107 incidents. The accident rate for the identified black spot on Soekarno Hatta Street in Bagan Besar Sub-District reached 0.727. Meanwhile, the black site on Cut Nyak Dien Street in Bangsal Aceh Village had an accident rate of 0.10.